(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Allah, the Creator, is the only Singular Super Force. A unified theory for the major forces gravity, weak, electromagnetic and strong nuclear forces is an intractable challenge to the scientists. This article is an innovative theory for unification of all forces in the universe; S-TOE. My published theory on quantum gravity was the first step. The main parameters and equations of the starting spherical singularity bubble of the early universe; acceleration, wavelength, radius, pressure and speed, were simply derived; named Sayed`s unified forces formula (SUFF). The violation of light speed at the early beginning of universe was dramatically found; 3.93 x 1027 m/s. The wavelength (λ) was also calculated and found to be 1.321 x 10-15 m. The difference, between the calculated force (9.29x1024 N) using SUFF and the Planck force (1.2103 x 1044 N) is might be due to contribution of other predicted forces. The calculated acceleration matches with Planck acceleration. Uniquely in this theory, the dark matter, dark energy and antimatter are among the acting forces control the universe. The Sayed`s forces diagram (SFD) is postulated and given. The anti-force term and concept is introduced to describe the opposite role of dark energy and matter. All the mentioned forces work together to keep the universe stable, expandable and equilibrium. Finally, it can be stated that some of the major universal constants need essential revision.